2016
DOI: 10.1007/s00737-016-0672-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile and maternal depression and anxiety symptoms in mid-pregnancy—the FinnBrain Birth Cohort Study

Abstract: Maternal prenatal psychological symptoms are associated with child health outcomes, e.g., atopic diseases. Altered prenatal functioning of the immune system is a potential mechanism linking maternal symptoms with child health. Research on prenatal distress and cytokines is warranted. The study population comprised consecutive N = 139 women from a general population-based FinnBrain Birth Cohort Study. Standardized questionnaires for depressive, overall anxiety, and pregnancy-related anxiety symptoms were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 65 publications
2
47
0
1
Order By: Relevance
“…Levels of IL-17 and other biomarkers were measured in all samples at the same time, blinded to treatment allocation and outcomes by the Microarray Core at UT Southwestern Medical Center using the Bioplex Pro ™ human cytokine standard 27-plex kit (Bio-Rad Laboratories, Hercules, CA, USA) with a Bio-plex ® 200 instrument that was equipped with Bio-Plex Manager software, version 6.0 (Bio-Rad Laboratory, Hercules, CA, USA). This commonly used (39, 40) 27-plex kit measures IL-17, Th1 (interferon gamma and tumor necrosis factor alpha), Th2 (IL-4, IL-5, IL-9, and IL-13), and non Th1/Th2 (IL-1 beta, IL-1 receptor antagonist, IL-8, IL-6, and macrophage inflammatory protein (MIP) 1 alpha and beta) markers, which were interpreted only if the intra- and inter-assays coefficients of variation were less than 10% of detection limits (or precision range) specified by manufacturer. The levels of IL-17 and other immune markers are expressed in pg/ml after correcting for 4-fold dilution using the standards provided in the kit (Bio-Rad Laboratory, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Levels of IL-17 and other biomarkers were measured in all samples at the same time, blinded to treatment allocation and outcomes by the Microarray Core at UT Southwestern Medical Center using the Bioplex Pro ™ human cytokine standard 27-plex kit (Bio-Rad Laboratories, Hercules, CA, USA) with a Bio-plex ® 200 instrument that was equipped with Bio-Plex Manager software, version 6.0 (Bio-Rad Laboratory, Hercules, CA, USA). This commonly used (39, 40) 27-plex kit measures IL-17, Th1 (interferon gamma and tumor necrosis factor alpha), Th2 (IL-4, IL-5, IL-9, and IL-13), and non Th1/Th2 (IL-1 beta, IL-1 receptor antagonist, IL-8, IL-6, and macrophage inflammatory protein (MIP) 1 alpha and beta) markers, which were interpreted only if the intra- and inter-assays coefficients of variation were less than 10% of detection limits (or precision range) specified by manufacturer. The levels of IL-17 and other immune markers are expressed in pg/ml after correcting for 4-fold dilution using the standards provided in the kit (Bio-Rad Laboratory, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that sleep disturbances, presenting as greater levels of insomnia, tiredness, and sleep loss, and as lessened general sleep quality, would be associated with a proinflammatory immune response. We have previously observed that maternal prenatal symptoms of depression and anxiety are positively associated with peripheral circulating cytokines IL-5, IL-9, and IL-13 in mid-pregnancy [26]. Also, as sleep disturbances are frequently observed in depression and anxiety, symptoms of depression and anxiety were controlled for in the present study [29].…”
Section: Introductionmentioning
confidence: 75%
“…The study population has been previously described [26] and, hence, only a brief description is given here. The study participants were drawn from a larger population-based pregnancy cohort, the FinnBrain Birth Cohort Study (www.finnbrain.fi) [31], currently ongoing in Southwest Finland.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations